2006
DOI: 10.1021/ja0572912
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Evaluation of [Ψ[CH2NH]Tpg4]Vancomycin Aglycon:  Reengineering Vancomycin for Dual d-Ala-d-Ala and d-Ala-d-Lac Binding

Abstract: An effective synthesis of [Ψ[CH 2 NH]Tpg 4 ]vancomycin aglycon (5) is detailed in which the residue 4 amide carbonyl of vancomycin aglycon has been replaced with a methylene. This removal of a single atom was conducted to enhance binding to D-Ala-D-Lac countering resistance endowed to bacteria that remodel their D-Ala-D-Ala peptidoglycan cell wall precursor by a similar single atom change (ester O for amide NH). Key elements of the approach include a synthesis of the modified vancomycin ABCD ring system featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
118
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 46 publications
2
118
0
6
Order By: Relevance
“…In a series of studies, we reported the first vancomycin analogs that contain changes at a key single-atom site in its target binding pocket (residue 4 carbonyl O → S, NH, H 2 ), the latter two of which were designed to directly address this underlying molecular basis of resistance to vancomycin ( Fig. 1) (43)(44)(45)(46)(47)(48)(49)(50). These rationally designed binding pocket modifications reinstated binding to the altered target D-Ala-D-Lac and maintained binding affinity for the unaltered target D-Ala-D-Ala.…”
Section: Significancementioning
confidence: 99%
“…In a series of studies, we reported the first vancomycin analogs that contain changes at a key single-atom site in its target binding pocket (residue 4 carbonyl O → S, NH, H 2 ), the latter two of which were designed to directly address this underlying molecular basis of resistance to vancomycin ( Fig. 1) (43)(44)(45)(46)(47)(48)(49)(50). These rationally designed binding pocket modifications reinstated binding to the altered target D-Ala-D-Lac and maintained binding affinity for the unaltered target D-Ala-D-Ala.…”
Section: Significancementioning
confidence: 99%
“…The conversion of D ‐Ala‐ D ‐Ala to D ‐Ala‐ D ‐Lac in the peptidoglycan termini is one of the mutations that provide resistance to native vancomycin, however, chemical modifications directed to key single‐atom sites in the binding pocket of vancomycin seem to enable the antibiotic to bind both the modified and the unaltered targets in the peptidoglycan (Crowley and Boger, 2006; Xie et al ., 2012; Okano et al ., 2015). Peripheral structural modifications, such as a (4‐chlorobiphenyl) methyl (CBP) group, increased the antimicrobial potency of vancomycin and provided, with multiple synergistic mechanisms of action, a delay in the emergence of resistance (Okano et al ., 2014, 2015).…”
Section: Highlightmentioning
confidence: 99%
“…Fig. 1) to avoid the unfavorable electrostatic interaction with the modified peptidoglycan terminal D-Ala-D-Lac [20,21]; b) the Nterminal was elongated in order to introduce an additional hydrogen-bonding with D-Ala-D-Lac [22]. In order to explore the possible conformational effect, hence the relative three-dimensional orientation of NHs, compound 2 and 3 having D-Leucine (found in vancomycin), and D-leucine, respectively, were synthesized; the glycine was attached to leucine terminal in order to incorporate depicted in the Fig.…”
Section: Antibiotic Activity Evaluationmentioning
confidence: 99%